Measuring the fiscal revenue loss of VAT exemption in commercial banking - Bernd Genser; Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The closing of tax loopholes is one important instrument for fiscal consolidation. We concentrate on the value added tax exemption of banking services in Germany. The potential tax revenue under full value added taxation cannot be estimated from national accounting data, as it is necessary to apportion the value added between final consumption and intermediate production. We develop a method which allows to base our estimates on disaggregated banks' balance sheet data and obtain an estimate for the lower bound of the net revenue loss of tax exemption to the order of 7 bill. DM in 1994.
Keywords: H2; G2; C8; 330; Umsatzsteuer; Bankgeschäft; Steuervergünstigung; Steuereinnahmen; Deutschland